THE FINE STRUCTURE, POTASSIUM CONTENT, AND RESPIRATORY ACTIVITY OF ISOLATED RAT LIVER PARENCHYMAL CELLS PREPARED BY IMPROVED ENZYMATIC TECHNIQUES - Howard, Roger B. (The Rockefeller University Press, 1973)
Further modifications of the enzymatic technique for the preparation of isolated, intact, parenchymal cells from rat liver as previously described by this laboratory are presented together with a detailed account of several critical factors involved during the procedure. In addition, the fine structure of the cells as revealed by electron microscopy and the characteristics of their respiratory activity in different media and with several added substrates are described. It is shown that cells obtained by adding calcium during the preparative procedure retain approximately 34% more potassium than cells prepared solely in a calcium-free medium. The former cells also demonstrate a higher respiratory activity, which is not due to uncoupling of respiration. Electron microscopy reveals that the cells have an intact plasma membrane and well-preserved intracellular organelles. Glycogen particles are observed in all cells and are particularly abundant when either 20 mM pyruvate is added during the preparation or Eagle's Minimum Essential Medium is employed.